Variety Learning Strategies in Early Childhood Islamic Education - Sujani, Elfara Hajjar (Proceeding International Conference on Religion, Science and Education, 2022)
Learning strategy is an essential element in teaching and learning activities. The use of appropriate strategies can make students interested, not bored, and excited, if it goes well then the learning outcomes will be obtained optimally. Various learning strategies can be implemented at the tertiary level, especially in the Department of Early Childhood Islamic Education (PIAUD). This study uses a literature study approach. This article examines various strategies that are suitable for PIAUD majors, ranging from Small Group Discussion (SGD), Role-Play and Stimulation, Case Study, Discovery Learning (DL), Cooperative Learning (CL), Collaborative Learning (CbL), Contextual Instruction (CI), Project Based Learning (PjBL) and Problem Based Learning (PBLI). Various existing strategies can be used and combined by lecturers when teaching so that the strategies used are not monotonous and so that students can explore in various fun ways. These learning strategies are not centered on the lecturer, so they can build students’ knowledge and creativity.